Racialized Governance: The Production and Destruction of Secure Spaces in Olympic Rio de Janeiro. Issue 1 (1st June 2020) - Ystanes, Margit; Magalhães, Alexandre
Abstract: Based on ethnographic fieldwork, this article explores the eviction of residents from Vila Autódromo, a neighborhood that was decimated as Rio de Janeiro prepared to host the 2016 Summer Olympics. Inspired by Achille Mbembe's notion of "necropolitics" and Mindy Fullilove's concept of "root shock, " we argue that forced evictions in Rio constitute a form of racialized governance. The authorities exclude favela residents from the citizenry security interventions are intended to protect and conceptualize them instead as security risks. This exclusion reflects the spatial expression of racial hierarchies in the city and produces a public security governance that in the case of Vila Autódromo terrorized residents and destroyed life conditions in their community. Racialized governance therefore exacerbates insecurity for large parts of the population.